Isolation and Identification of Candida sp. in Vagina of Long-Tailed Macaque (Macaca fascicularis) - Zico, Hanifa; Erina, Erina; Balqis, Ummu; Rahmi, Erdiansyah; NA, Zuhrawaty (Pelopor Publikasi Akademika, 2024)
Candida sp. are commonly found as normal flora in vagina and in certain conditions are opportunistic pathogen. This study aimed to isolation and identification Candida sp. in vagina of the long-tailed macaque (Macaca fascicularis). The sample used in the study was a vaginal swab from five long-tailed macaque (Macaca fascicularis) from Seulawah Forest Aceh Besar. Identification of Candida sp. observed macroscopically by looking at the differences in the color of the colonies grown on the CHROMagar-Candida media. The data obtained were analyzed descriptively. The results of the examination showed that in the vagina of the long-tailed macaque (Macaca fascicularis) there were six species of Candida sp. like C. albicans, C. krusei, C. tropicalis, C. glabrata, C. dubliniensis and C. parapsilosis. It can be concluded that there are several species of Candida sp. which was successfully isolated and identified in vagina of a long-tailed macaque (Macaca fascicularis).